2018
DOI: 10.1186/s13568-018-0542-2
|View full text |Cite
|
Sign up to set email alerts
|

Conformational determinants necessary for secretion of Paecilomyces thermophila β-1,4-xylosidase that lacks a signal peptide

Abstract: In this study, we investigated the secretion mechanism of the hyper-secretion signal peptide-lacking β-xylosidase PtXyl43, a non-classically secreted protein, from the fungus Paecilomyces thermophila in Escherichia coli BL21(DE3). PtXyl43 secretion is a two-step process, and the second step is accompanied by cell periplasmic leakage, indicating that PtXyl43 secretion is the result of semi-specific secretion. Homology modeling of PtXyl43 suggested that PtXyl43 had a canonical GH43 family β-xylosidase structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…16 Xylans are composed of 1,4-linked xylosyl residues having a side chain of various acids like D-glucuronic, arabonic, p-coumaric, ferulic and acetic at 2,3-OH positions. 17,18 Hemicellulases are a group of enzymes which are classied according to their substrates. The synergistic action of various enzymes is necessary to hydrolyze cellulose and hemicelluloses.…”
Section: Introductionmentioning
confidence: 99%
“…16 Xylans are composed of 1,4-linked xylosyl residues having a side chain of various acids like D-glucuronic, arabonic, p-coumaric, ferulic and acetic at 2,3-OH positions. 17,18 Hemicellulases are a group of enzymes which are classied according to their substrates. The synergistic action of various enzymes is necessary to hydrolyze cellulose and hemicelluloses.…”
Section: Introductionmentioning
confidence: 99%
“…cellulase could act as the atypical signal peptide for transportation by E. coli . Yang et al (2018) proved that the conformational signal of Paecilomyces thermophila β-1, 4-xylosidase played important role for secretion in E. coli . These results suggested that the secretion mechanism was specific for different proteins.…”
Section: Discussionmentioning
confidence: 99%